LENGTH-WEIGHT RELATIONSHIP AND HEALTH OF Macrobrachium dux (LENZ, 1910) AND Macrobrachium macrobrachion (HERKLOTS, 1851) IN RIVER ETHIOPE HEADWATERS, NIGERIA - ISIOMA, ILOBA, KATE; ZINO, OTOKUEFOR, JEMINE; ISRAEL, OYEDOKUN SUNDAY (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The length-weight relationship and condition factor of two identified Palaemonidae species, Macrobrachium dux (Lenz, 1910) and Macrobrachium macrobrachion (Herklots, 1851) from the upper limnic River Ethiope, Nigeria, were investigated for future aquaculture feather nest and management. Prawn samples were collected from three sites (Umutu, Abraka, and Eku) by artisanal fishers using local traps and scooping gear. Of the 285 prawns collected from artisanal, 238 (83.51%) were allotted to Abraka and Eku registered 47(16.49%). The prawns were identified using the taxonomic keys. The total length of the prawns was measured to the nearest 0.01 cm with a pair of dividers and a metre rule. The weights of the shrimp were also taken using the OHAUS dial spring scale to the nearest 0.1g. The length-frequency analyses showed the males ranged from 4.1-6.5cm in length, with a weight range of 0.51-2.63g, mostly more massive than the females (1.5-5.3cm) with a higher weight range (0.03-12.0g) and the non-identified sex (NIS) group with a 0.1-2.9cm length range. Only the NIS of M.dux at Eku showed positive allometric growth (b > 3), while the others showed negative allometry (b 3). High correlation determinants (r²) exist between the length-weight of all species besides the female M.dux at Abraka (0.26) and Eku (0.33). The condition factors of the two prawns predicted upper River Ethiope soft water quality as good for farming M.dux and M. macrobrachion.